UPAYA PENINGKATAN KESADARAN MEREK UNIQLO PADA GENERASI Z - Grazella Bella Pradanti; Diana Aqmala; Mochammad Eric Suryakencana Wibowo; Fakhmi Zakaria (Universitas Pasundan, 2025)
Globalization and advances in the retail industry have driven the rapid growth of fast fashion in Indonesia, with Uniqlo as one of the major players. This research aims to analyze the influence of social media, product innovation, and brand collaboration on Uniqlo brand awareness among Generation Z in Semarang City. Using a quantitative approach, data was collected using a questionnaire with purposive sampling techniques from 121 Generation Z respondents in Semarang City who are Uniqlo product users. The results of the study show that social media has a positive and significant effect on brand awareness, product innovation has a positive and significant effect on brand awareness, and brand collaboration has a positive and significant effect on brand awareness. Further research is recommended to compare the effectiveness of Instagram and TikTok social media in building brand awareness and to examine differences in consumer behavior across cities and generations. The results of this study are expected to serve as a reference for Uniqlo in improving its marketing strategies, product innovation, and brand collaboration so that brand awareness can be optimized among Generation Z.